The effect of ethanol, petrol and rapeseed oil blends on direct injection diesel engine performance and exhaust emissions - Labeckas, Gvidonas; Slavinskas, Stasys (Transport, 2010)
The article deals with the testing results of a four stroke four cylinder, DI diesel engine operating on pure rapeseed oil (RO) and its 2.5vol%, 5vol% and 7.5vol% blends with ethanol (ERO) and petrol (PRO). The purpose of this study is to examine the effect of ethanol and petrol addition to RO on blend viscosity, percentage changes in brake mean effective pressure (bmep), brake specific fuel consumption (bsfc), the brake thermal efficiency (çe) of a diesel engine and its emission composition, including NO, NO2, NOX, CO, CO2, HC and the smoke opacity of exhausts. The addition of 2.5, 5 and 7.5vol% of ethanol and the same percentage of petrol into RO, at a temperature of 20 °C, diminish the viscosity of the blends by 9.2%, 21.3%, 28.3% and 14.1%, 24.8%, 31.7% respectively. Heating biofuels up to a temperature of 60 °C, diminishes the kinematic viscosity of RO, blends ERO2.5–7.5 and PRO2.5–7.5 4.2, 3.9–3.8 and 3.9–3.7 times accordingly. At a speed of 1400–1800 min‐1, bmep higher by 1.3% if compared with that of RO (0.772–0.770 MPa) ensures blend PRO2.5, whereas at a rated speed of 2200 min‐1 , bmep higher by 5.6–2.7% can be obtained when fuelling the loaded engine, ë = 1.6, with both PRO2.5–5 blends. The bsfc of the engine operating on blend PRO2.5 at maximum torque and rated power is respectively 3.0% and 5.5% lower. The highest brake thermal efficiency at maximum torque (0.400) and rated power (0.415) compared to that of RO (0.394) also suggests blend PRO2.5. The largest increase in NOXemissions making 1907 ppm (24.8%) and 1811 ppm (19.6%) compared to that of RO was measured from a more calorific blend PRO7.5 (9.99% oxygen) at low (1400 min‐1) and rated (2200 min‐1) speeds. The emission of carbon monoxide from blends ERO2.5–5 throughout the whole speed range runs lower from 6.1% to 32.9% and the smoke opacity of the fully loaded engine changes from 5.1% which is a higher to 46.4% which is a lower level if compared to the corresponding data obtained using pure RO. The CO2 emissions of carbon monoxide and the temperature of the exhausts generated by the engine running at a speed of 2200 min‐1 diminish from 7.8 vol% to 6.3vol% and from 500 °C to 465 °C due to the addition of 7.5vol% of ethanol to RO. First published online: 24 Jun 2011